Reproductive Management of Peruvian Grunt Anisotremus scapularis in Captivity: Spawning Dynamics, Hatching Rate, and Larval Survival - Jordan I. Huanacuni; Renzo Pepe-Victoriano; Pablo Presa; Luis A. Espinoza-Ramos (Animals)
The Peruvian grunt, Anisotremus scapularis, is a commercially valuable coastal fish in the southeastern Pacific that is facing overexploitation. To support its aquaculture development, this study evaluated the spontaneous reproductive dynamics of a captive broodstock held under natural photoperiod and temperature conditions in a flow-through system. Eleven wild adult specimens (3 females and 8 males) with an average size of 34.9 ± 5.4 cm and a weight of 986 ± 470 g were housed in a 9 m3 tank and monitored over five consecutive spawning seasons (2016–2021). Fish were fed a semi-moist, animal-protein-based diet (37% protein and 6.6% lipid) at 2% body weight/day. A total of 214 spontaneous spawning events produced over 83 million eggs. The highest reproductive output occurred in the first season (2016–2017) with 94 spawnings and 23.3 million eggs. Fertilization, hatching, and larval survival rates averaged 94.7%, 89.7%, and 75%, respectively, but declined in later years. Spawning showed marked seasonality from October to May, with a major reproductive pause in late January. The temperature (16–20 °C) and photoperiod (>12 h daylight) appeared to influence reproductive timing, alongside diet and broodstock handling. The findings reported herein are observational in nature and provide valuable baseline data for future experimental designs aimed at optimizing broodstock management in A. scapularis aquaculture.